Reachable workspace analysis is a potential measurement for impairment of the upper extremity in neuralgic amyotrophy. Issue 3 (21st June 2022) - IJspeert, Jos; Lustenhouwer, Renee; Janssen, Renske M.; Han, Jay J.; Hatch, Maya N.; Cameron, Ian; Helmich, Rick C.; van Engelen, Baziel; van der Wees, Philip; Geurts, Alexander C. H.; van Alfen, Nens; Groothuis, Jan T.
Abstract: Introduction/Aims: Neuralgic amyotrophy (NA) is a multifocal neuropathy involving the nerves of the upper extremity, limiting functional capability and reducing range of motion. The reachable workspace (RWS) is a computerized three‐dimensinal analysis system that evaluates the relative surface area (RSA) of an individual's arm reachability and has shown utility in several neuromuscular disorders. The aims of this study were to examine the ability of the RWS to quantitatively detect limitations in upper extremity active range of motion in patients with NA, and correlate these with other upper extremity functional outcome measures. Methods: Forty‐seven patients with NA and 25 healthy age‐ and sex‐matched controls were measured with the RWS. Study participants' RSAs were correlated with scores on the Shoulder Rating Questionnaire (SRQ), the Disabilities of Arm Shoulder and Hand (DASH) questionnaire, and upper extremity strength measurements using hand‐held dynamometry. Results: Patients with NA showed significantly lower values in the affected arm for all quadrants (except for the ipsilateral lower quadrant) and total RSA compared with controls ( P < 0.001). We found moderate correlations between the reachable workspace, the DASH questionnaire result (r = −0.415), and serratus anterior muscle strength ( r = 0.414). Discussion: RWS is able to detect limitations in active range of motion of the affected arm in patients with NA, and is moderately correlated with upper extremity functional measures. RWS can demonstrate impairment of the affected upper extremity in NA and it has potential as a clinical outcome measure.